(untitled) (Research, Society and Development, 2022)
In order to produce a food more attractive the food industry utilize dyes, which are one of the major classes of essential additives for food products. Regarding natural dyes, the anthocyanins are the one of the largest and main groups of pigments. Microencapsulation is a technology used to protect products of interest from interference such as light and oxygen, among others, and the encapsulant acts as a protective matrix. Thus, the aim of this study was to obtain the proximal composition of the red corn (Zea mays L.) kernels, to characterize the extract of the pericarp of the red corn in relation to the antioxidant activity and to obtain and characterize microcapsules of the pericarp of red corn extract by spray drying using gum arabic as wall material. It was evaluated the microcapsules in relation to water activity, moisture, yield of powder, solubility, wettability, encapsulation efficiency, anthocyanin retention, color and parameters and morphology. In addition, the corn grain was analyzed to obtain the centesimal composition and the characterization of the pericarp extract of red corn was carried out. As results, the powder presented low moisture and water activity, which is ideal for a product to maintain a high shelf life. The yield value was high, as well as the microcapsules solubility and wettability. The analysis of the color showed similar results for pericarp and microcapsules in both cases tending towards to red color. In conclusion, the use of microcapsules produced by red corn pericarp extract may become viable alternative as food natural dye.